LogTracker: Learning Log Revision Behaviors Proactively from Software Evolution History - Li, Shanshan; Niu, Xu; Jia, Zhouyang; Wang, Ji; He, Haochen; Wang, Teng (2018 IEEE/ACM 26th International Conference on Program Comprehension (ICPC), 2018)
Log statements are widely used for postmortem debugging. Despite the importance of log messages, it is difficult for developers to establish good logging practices. There are two main reasons for this. First, there are no rigorous specifications or systematic processes to guide the practices of software logging. Second, logging code co-evolves with bug fixes or feature updates. While previous works on log enhancement have successfully focused on the first problem, they are hard to solve the latter. For taking the first step towards solving the second problem, this paper is inspired by code clones and assumes that logging code with similar context is pervasive in software and deserves similar modifications. To verify our assumptions, we conduct an empirical study on eight open-source projects. Based on the observation, we design and implement LogTracker, an automatic tool that can predict log revisions by mining the correlation between logging context and modifications. With an enhanced modeling of logging context, LogTracker is able to guide more intricate log revisions that cannot be covered by existing tools. We evaluate the effectiveness of LogTracker by applying it to the latest version of subject projects. The results of our experiments show that LogTracker can detect 199 instances of log revisions. So far, we have reported 25 of them, and 6 have been accepted.